2015
DOI: 10.1111/add.12899
|View full text |Cite
|
Sign up to set email alerts
|

Global statistics on addictive behaviours: 2014 status report

Abstract: Conflict of interest declaration: RW undertakes research and consultancy for companies that develop and manufacture smoking cessation medicines. AbstractBackground and aims: Addictive behaviours are among the greatest scourges on humankind. It is important to estimate the extent of the problem globally and in different geographical regions. Such estimates are available but there is a need to collate and evaluate these to arrive at the best available synthetic figures. Addiction has commissioned this paper as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
207
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(233 citation statements)
references
References 18 publications
5
207
0
13
Order By: Relevance
“…More broadly, we note that the number of international bodies collecting information on aspects of drug use has prompted calls for more system wide coherence. We would therefore concur with the conclusions of Gowing et al [21] that there is an 'urgent need to review the quality of data on which global estimates are made and coordinate efforts to arrive at a more consistent approach' (p. 918). We would argue that the European experience highlights not only the challenges that this entails but also the considerable potential over the longer term to provide a more robust understanding of an increasingly global, dynamic and complex drug situation.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…More broadly, we note that the number of international bodies collecting information on aspects of drug use has prompted calls for more system wide coherence. We would therefore concur with the conclusions of Gowing et al [21] that there is an 'urgent need to review the quality of data on which global estimates are made and coordinate efforts to arrive at a more consistent approach' (p. 918). We would argue that the European experience highlights not only the challenges that this entails but also the considerable potential over the longer term to provide a more robust understanding of an increasingly global, dynamic and complex drug situation.…”
Section: Resultssupporting
confidence: 85%
“…The European data therefore contain many of the elements found in other national and international reporting systems. A review of global addiction data sources with comments on their relative strengths and weakness is provided by Gowing et al [21]. It is worth noting, in particular, that the reporting mechanism supporting the United Nations (UN) drug conventions (Annual Report Questionnaire) covers the main information domains for both demand and supply data included in the European data set.…”
Section: The European Data In An International Contextmentioning
confidence: 99%
“…Studies have shown that alcohol use is related detrimentally too many cardiovascular problems, including hypertension, hemorrhagic stroke and atrial fibrillation [22]. Consumption of alcohol has also been implicated in other conditions like cancers, fetal alcohol syndrome and diabetes mellitus [23].…”
Section: Discussionmentioning
confidence: 99%
“…These individuals are often younger and are more likely to be working and in stable housing. We need to ensure that provision for these individuals is tailored and responsive (HM Government, 2010:6) There has been growing interest in the demographic changes in drug use, and the potential impact this will have on successful treatment outcomes (Badrakalimuthu et al 2010, Gowing et al 2015. The Royal College of Psychiatrists (2011) recently examined this issue making a number of recommendations including the need for the 'examination of trends in the extent, nature and predictors of substance use problems in older people'.…”
Section: Figure 1 Herementioning
confidence: 99%